Osteocytes function as biomechanical signaling hubs bridging mechanical stress sensing and systemic adaptation - Yuze, Ma; Hu, Jin; Jun, Lv; Cheng, Xu; Tianwen, Xin; Junqiang, Zhang (Frontiers in Physiology, 2025)
Osteocytes, the most abundant bone cells embedded within mineralized matrix, are pivotal regulators of skeletal and systemic homeostasis. Recent advances highlight their mechanotransductive roles via mechanosensors, enabling detection of mechanical stimuli and conversion into biochemical signals to orchestrate bone remodeling. Beyond bone, osteokines derived from osteocytes engage themselves in bidirectional crosstalk with distant organs or tissues—modulating brain, liver, kidney, muscle, adipose tissue, nerve, blood vessel, and cancer. Hormonal and metabolic effects further integrate osteocyte activity into systemic regulation, while pathologies like diabetes or mechanical unloading disrupt their viability and signaling. Emerging evidence positions osteocytes as central hubs in interorgan networks, with neuron-like morphology enhancing their mechanosensing and communicative capacity. Understanding osteocyte-centric regulatory axes offers novel insights into bone-related diseases and systemic homeostasis.